Nano Online 2016
DOI: 10.1515/nano.12951_2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon black nanomaterial on biological membranes revealed by shape of human erythrocytes, platelets and phospholipid vesicles

Abstract: BackgroundRecent advances in development and industrial production of nanomaterials require assessment of their effects on human and animal health. Toxicity of nanomaterials has therefore become an issue regarding the question which methods are the most appropriate for determining health risk [1,2]. Nanomaterial introduces also effects that cannot be explained by composition of the material and chemical reactions, but require consideration of non-specific properties, such as size and shape of particles, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In an earlier study, it was possible for Nemmar et al to assess thrombus formation in vivo using an online video camera after staining the tissue with Rose Bengal, to determine the size of the developing thrombus from light intensity (234). In 2015 Pajnič et al observed the in vitro alteration in the membrane structure of blood cells when exposed to different nanomaterials, such as carbon black, through SEM analysis (248).…”
Section: Bind Et Al Detected An Association Between Pm On Plasma Fibrinogen Levels In a Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study, it was possible for Nemmar et al to assess thrombus formation in vivo using an online video camera after staining the tissue with Rose Bengal, to determine the size of the developing thrombus from light intensity (234). In 2015 Pajnič et al observed the in vitro alteration in the membrane structure of blood cells when exposed to different nanomaterials, such as carbon black, through SEM analysis (248).…”
Section: Bind Et Al Detected An Association Between Pm On Plasma Fibrinogen Levels In a Cohortmentioning
confidence: 99%
“…Cardiovascular disease is one of the leading causes of death across the world with approximately 30% of deaths being reported in relation to cardiovascular episodes(266,267). Between 2007 and 2017, total deaths from cardiovascular disease increased globally by 21.1%(268).Whilst nanoparticles have been employed in the treatment of blood disorders and disease(249,250,255,256), a wealth of research has indicated that diesel PM of a similar size, produced due to incomplete combustion, increase the likelihood of adverse effects on blood coagulation(161,168,192,201,224,230,235,236,269). The effects of particulates on coagulation has previously been monitored using techniques involving measurement of a clotting time, microscopy and platelet function tests(161,168,224,234).…”
mentioning
confidence: 99%